Impact of environmental and physiological parameters on antioxidant activity in Premna Serratifolia L. - Chua, Iris Yien Ping (2014)
Premna serratifolia L. is believed to have antioxidant properties. However, the scientific research on this species is still lacking. This study was conducted to assess the influence of environmental (light intensity, air temperature, relative humidity) and physiological (photosynthetic rate, transpiration rate and stomata conductance) parameters on the antioxidant content in P. serratifolia L.. Fresh leaves at the lower part of P. serratifolia L. were collected at 6 am, 9 am, 12 noon, 3 pm and 6 pm on the third consecutive sunny day at the botanical garden, Universiti Putra Malaysia Bintulu Sarawak Campus. Light intensities, air temperature (Ta), relative humidity (RH), photosynthetic rate (A), stomata conductance (gs) and transpiration rate (E) of P. serratifolia L. were measured in situ on the day of leaf collection. The antioxidant activities were measured by 1,1-diphenyl-2- picryhydrazyl (DPPH) radical method while total flavonoid (TF) content and total phenolic (TP) were estimated by using aluminium chloride reagent and Folin-Ciocalteu reagent, respectively. The antioxidant compounds present in the leaf extracts of P. serratifolia L. with the highest or lowest antioxidant activity (accessed by DPPH antioxidant activity, TP and TF content) was identified by using High Performance Liquid Chromatography (HPLC). Results showed that leaf extracts collected at 9 am had the highest DPPH antioxidant activity and the lowest TF and TP contents. On the other hand, leaf extracts collected at 12 noon had the highest TF and TP contents but the lowest DPPH antioxidant activity. Correlation test showed that DPPH antioxidant activity, TF and TP content were influenced significantly by air temperature. However, other environmental parameters, namely light intensities and physiological parameters were not significantly correlated with DPPH antioxidant activity, TF and TP content in P. serratifolia L.. Antioxidant compounds were divided into heat induced and non-heat induced as some antioxidant compounds were found to be significantly correlated with temperature. The identified antioxidant compounds that were possibly heat induced included theaflavins, epigallocatechin, epicatechin and ascorbic acid while the non-heat induced were catechin, quercetin, uric acid and rutin. In conclusion, consideration on environmental parameter, namely air temperature is crucial in order to obtain high antioxidant compounds.